![\dfrac{24}{x^2+2x-8}-\dfrac{15}{x^2+2x-3}=2 \dfrac{24}{x^2+2x-8}-\dfrac{15}{x^2+2x-3}=2](https://tex.z-dn.net/?f=%5Cdfrac%7B24%7D%7Bx%5E2%2B2x-8%7D-%5Cdfrac%7B15%7D%7Bx%5E2%2B2x-3%7D%3D2)
Знаменатель 1-й дроби:
x² + 2x - 8 = x² + 2x + 1 - 9 = (x + 1)² - 9
Знаменатель 2-й дроби:
x² + 2x - 3 = x² + 2x + 1 - 4 = (x + 1)² - 4
Заменим (x + 1)² - 9 буквой t, то есть положим (x + 1)² - 9 = t, тогда (x + 1)² - 4 = t + 5
получаем уравнение:
![\dfrac{24}{t}-\dfrac{15}{t+5}=2 \dfrac{24}{t}-\dfrac{15}{t+5}=2](https://tex.z-dn.net/?f=%5Cdfrac%7B24%7D%7Bt%7D-%5Cdfrac%7B15%7D%7Bt%2B5%7D%3D2)
t ≠ 0; t ≠ -5
![\dfrac{24t+120-15t}{t^2+5t}=\dfrac{2}{1} \dfrac{24t+120-15t}{t^2+5t}=\dfrac{2}{1}](https://tex.z-dn.net/?f=%5Cdfrac%7B24t%2B120-15t%7D%7Bt%5E2%2B5t%7D%3D%5Cdfrac%7B2%7D%7B1%7D)
9t + 120 = 2t² + 10t
2t² + 10t - 9t - 120 = 0
2t² + t - 120 = 0
D = 1 + 4 · 2 · 120 = 961 = 31²
t₁₂ = (-1 ± 31) / 4
t₁ = -8; t₂ = 7,5
Возврат к переменной x:
1) (x + 1)² - 9 = -8 или 2) (x + 1)² - 9 = 7,5
1) (x + 1)² = 1; x + 1 = ±1; x = -2 или x = 0
2) (x + 1)² = 33/2; x + 1 = ±√(33/2); x = -1 ± √(33/2)
Ответ:
-1 ± √(33/2); -2; 0